Broad forbidden Ne III line emission and intermediate-density gas around QSO nuclei - Zheng, Wei; Burbridge, E. Margaret; Smith, Harding E. (Publications of the Astronomical Society of the Pacific, 1990)
A broad emission feature, with a velocity width of the order of 5000 km/s, has been observed near rest wavelength 3870 A in the spectra of three low-redshift QSOs. The line is identified as forbidden Ne III 3869. This broad line may have varied over a time scale of two years, indicating that clouds of intermediate density between 10 to the 8th and 10 to the 11th/cu cm may coexist in the broad-line region. Such clouds would be optically thin, highly ionized, and subject to rapid destruction by radiation pressure.